FERREDOXIN OF CLOSTRIDIUM THERMOSACCHAROLYTICUM - Wilder, Martin (J Bacteriol, 1963)
Wilder, Martin (University of Kansas, Lawrence), R. C. Valentine, and J. M. Akagi. Ferredoxin of Clostridium thermosaccharolyticum. J. Bacteriol. 86:861–865. 1963.—An electron-transferring agent has been isolated from Clostridium thermosaccharolyticum. This factor was found to participate as an electron carrier in the phosphoroclastic reaction of pyruvate, with the subsequent formation of acetyl phosphate and molecular hydrogen. It can be employed interchangeably with the ferredoxin of C. pasteurianum in various reactions. Thermal-stability studies indicated that this factor from C. thermosaccharolyticum was comparatively more heat-resistant than the carrier obtained from C. pasteurianum. It was concluded that this carrier was ferredoxin or a ferredoxin-like substance.